Multiple Fat- Containing Hepatic Hydatid Cysts: A Case Report in The X- Ray Institute at Medical City Health Directorate in Iraq - Tariq Abdul-Wahaab , Issam; A Hadi , Khaleel; Abdulameer Ghayad , Haider (Diyala Journal of Medicine, 2021)
Background: Hydatidosis is a zoonotic disease caused by Echinococcus granulosus and Echinococcus multilocularis parasite which is still endemic in many countries all over the world especially in the developing countries. The liver is the primary site to be infested by the parasite with a rate of 60 – 75%. The right lobe of the liver gets infected in about 80% of cases. Hydatid disease of the liver is usually asymptomatic and most cases discovered accidentally on routine clinical or radiological examinations for other illness. Symptoms usually appear in complicated cases either due to rupture, secondary bacterial infection, or due to the large size of the cyst which might cause pain in the right upper quadrant of the abdomen, discomfort, and sometimes swelling. In this case report, we reported the presence of fat globules within the hepatic hydatid cysts which is most probably due to rupture of hepatic hydatid cysts into the biliary tree.